1966
DOI: 10.1063/1.1726787
|View full text |Cite
|
Sign up to set email alerts
|

Atomic View of Surface Self-Diffusion: Tungsten on Tungsten

Abstract: Surface diffusion of tungsten adatoms on several smooth, low-index planes of the tungsten lattice has for the first time been followed by direct observation of individual atoms in the field-ion microscope. Contrary to expectation, the mobility at room temperature is found to increase in the order (211) > (321) ∼ (110) > (310) ∼ (111). Migrating atoms are reflected at the boundaries of the (110), (211), and (321) planes; on the latter two, motion along atomic rows is favored over diffusion across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
798
0
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,669 publications
(830 citation statements)
references
References 10 publications
24
798
0
8
Order By: Relevance
“…1, [48][49][50] Extensive research can be found in the literature on the kinetic instability. The step edge barriers also modify the mobility for the surface evolution under elastic effects.…”
Section: Introductionmentioning
confidence: 99%
“…1, [48][49][50] Extensive research can be found in the literature on the kinetic instability. The step edge barriers also modify the mobility for the surface evolution under elastic effects.…”
Section: Introductionmentioning
confidence: 99%
“…13 A potentially attractive and unique feature of high-power pulsed magnetron sputtering (HIPIMS) 14 is the ability to ionize up to 90% of the sputtered metal flux, 15 depending upon the metal. Thus, HIPIMS offers the opportunity to increase momentum transfer to the growing film, while providing enhanced adatom mobilities and higher probabilities for overcoming Ehrlich step-edge barriers, 16,17,18,19 utilizing sputtered metal atoms which are ionized in the plasma. 20 Here, we report results of an investigation of the growth of polycrystalline Ti 1-x Al x N films by co-sputtering from separate elemental metal targets, Al and Ti, in a hybrid HIPIMS/DCMS configuration in order to selectively control the composition of metal ion fluxes during ionassisted growth.…”
Section: Introductionmentioning
confidence: 99%
“…4(b) of Ref. [2]. In addition, in the same STM image one can see modulation of the widths of worm-like pyramids (pearl-like substructures), corresponding to the arrays of small rounded mounds in Fig.…”
mentioning
confidence: 75%
“…Of paramount significance are adatom interactions with steps that form on the multilayered surface, particularly the energy barriers occurring near the step edges that inhibit adatom transitions between layers of the growing interface. These so-called step edge barriers were found by Ehrlich and Hudda [2], and further elucidated by Schwoebel [3] and Villain [4]. Ehrlich-Schwoebel-Villain (ESV) energy barriers produce up-hill adatom surface currents, from the terrace of the lower layer towards the terrace of the upper layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation